A PRAYER FOR CONTENTMENT - Hendro (Jurnal Amanat Agung, 2015)
Proverbs 30 contains the only prayer in the Book of Proverbs – a prayer of contentment. Contentment appears to be a theme consistently taught in the Old Testament and the New Testament. It was discontentment toward God that drove Eve and Adam to eat the fruit of the tree of knowledge of good and evil. And until this day, it was our discontentment with God, ourselves, and others, that drove us searching around desperately.